Agrobacterium-mediated Genetic Transformation in Lentil (Lens culinaris Medik.) followed by In vitro Flowering and Seed Formation (Plant Tissue Culture and Biotechnology, 2012)
Genetic transformation system was developed for two microsperma varieties of lentil (Lens culinaris Medik.), namely Bari Masur-4 (BM-4) and Bari Masur-5 (BM-5) using Agrobacterium tumefaciens strain LBA4404 harbouring binary plasmid pBI121, containing GUS and nptII genes. Three different types of embryo explants, namely cotyledonary node (CN), decapitated embryo (DE) and cotyledone attached decapitated embryo (CADE) were used. Highest GUS positive expression was found in DE followed by CADE as detected by transient assays. Following Agrobacterium infection CADE showed better response in developing multiple shoots on MS supplemented with 2.22 µM BAP, 2.32 µM Kn, 0.29 µM GA3 and 30.35 µM tyrosine. Selection of the transformed shoots was carried out by gradually increasing the concentration of kanamycin up to 200 mg/l. Transgenic lentil shoots were produced with an overall frequency of 1.009%. In vitro rooting appeared to have a limitation in obtaining complete plantlets in lentil, therefore in vitro flowering and seed formation were induced in transformed shoots of lentil with a view to recovering of the transgenic progenies.  GUS positive shoots were found to produce in vitro flowers and pods on half-strength MS containing 98.4 µM IBA and 2.69 µM NAA. Expression of gene was detected in various tissues of the transformed shoots. Stable integration of GUS gene was also confirmed through PCR analysis. Plant Tissue Cult. & Biotech. 22(1): 13-26, 2012 (June) DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11243